Reliability assessment of indicators measuring the impact of enterprise risk management on performance of higher education institutions in Sri Lanka / Angage Anoma Samanthi Perera ... [et al.] - Perera, Angage Anoma Samanthi; Rahmat, Abdul Khabir; Khatibi, Ali; Ferdous Azam, S. M. (Universiti Teknologi MARA, 2022)
Higher educational institutions are exposed to various types of risks what other entities face naming strategic, operational, financial, compliance, technological and reputational risk owing to terrifying competition, rapid technological advancements and unpredictable environmental tremors. Implementation of enterprise risk management is the best strategic tool to identify, assess and mitigate the overall risks faced by entities. The implementation of enterprise risk management is however hindered by the high cost for ERM systems implementation and the inability of justification of increasing performances. Many research studies conducted by academicians and practitioners to ascertain the significant positive relationship of Enterprise Risk Management implementation and firm performance concluded with contradictory deductions. This study is an investigation of the reliability of the indicators measuring the impact of ERM implementation on the performance of non-state higher education institutions in Sri Lanka. The sample of hundred and seventy senior professionals was selected from the study population of seven hundred and seven senior persons attached to non-state institutions in Sri Lanka using stratified random sampling technique. This paper presents the outcomes of the quantitative investigation conducted to test the reliability of the indicators that were used to measure the latent variables in the survey instrument. As the Cronbach’s alpha value of each latent variable was well above the threshold of 0.70, the items used in each variable were fitting to the construct and therefore accepted as reliable indicators to measure the constructs.